ChemInform Abstract: Toward the Stereoselective Synthesis of C1—C23 Fragment of Spirastrellolide B. Issue 2 (January 2015) - Rajesh, Akkapalli; Sharma, Gangavaram V. M.; Damera, Krishna
Abstract The key steps of the synthesis of the title fragment (I) are cross metathesis and Bu4NF promoted oxa‐Michael reaction.